Galvanic replacement-mediated synthesis of Pd–Cu alloy nanospheres as electrocatalysts for formic acid oxidation. (June 2022) - Tai, X.; Wu, B.; Bao, J.; Qu, W.; Zhao, L.; Wang, Z.
Abstract: Rational synthesis of bimetallic electrocatalysts with the special geometric structure for direct formic acid fuel cells remains yet challenging. Herein, a facile synthetic strategy is presented to prepare the bimetallic Pd–Cu alloy nanospheres (Pd–Cu ANSs) catalysts based on the galvanic replacement and high-temperature reconstruction. The formation mechanism of Pd–Cu ANSs is studied thoroughly from comprehensive characterizations and control experiments. The optimized Pd–Cu ANSs with unique nanosphere structure as well as regulated electronic structure provide excellent electrocatalytic performance for formic acid oxidation reaction (FAOR) with a specific activity of 6.11 mA cm - 2 Pd and mass activity of 1569.48 mA mg -1 Pd, which are 2.7 times and 3.5 times as high as these of the Pd/C catalyst. This synthetic method outlined here could provide a new pathway for noble metal-based alloy nanomaterials for diverse applications. Graphical abstract: Image 1 . Highlights: Pd–Cu alloy nanospheres were prepared via a facile synthetic strategy involving galvanic replacement reaction and pyrolysis treatment. The evolution process of Pd–Cu alloy nanospheres from cube-shaped Cu2 O templates was studied thoroughly. The as-synthesized catalysts performed enhanced FAOR performance with a SA of 6.11 mA cm -1 Pd and MA of 1569.48 mA mg -1 Pd .